Методологія перевірки математичних моделей функціонування агромостових систем на адекватність - Кувачов, Володимир Петрович; Кувачев, Владимир Петрович; Kuvachov, Volodymyr; Мітков, Василь Борисович; Митков, Василий Борисович; Mitkov, Vasyl; Ігнатьєв, Євген Ігорович; Игнатьев, Евгений Игоревич; Ihnatiev, Yevhen; Аюбов, Абдулмелік Мухтарович; Аюбов, Абдулмелик Мухтарович; Aiubov, Abdulmelik (ТДАТУ, 2020)
UK: В статті проведено апробацію методології перевірки на адекватність результатів математичного моделювання функціонування спеціалізованих ширококолійних агрозасобів мостового типу з використанням положень теорії автоматичного регулювання динамічних систем. Перевірку математичних моделей горизонтальних і вертикальних коливань спеціалізованого ширококолійного агрозасобу на адекватність здійснено шляхом порівняння теоретичних та експериментальних амплітудно-частотних характеристик коливань курсового його кута і поперечного зміщення, а такожтеоретичної і експериментальної нормованих спектральних щільностей вертикальних коливань його остова (як вихідних величин) при відпрацюванні ним вхідних збурюючих впливів. Результатом кількісного оцінювання досліджуваних характеристик встановлено, що за F-критерієм Фішера нуль-гіпотеза про рівність порівнювальних дисперсій вихідних величин не відхиляється. Задовільний збіг теоретичних та експериментальних результатів, а також позитивний результат перевірки математичних моделей вертикальних та горизонтальних коливань агрозасобу на адекватність вказує на можливість їх подальшого використання для вирішення наукових та практичних задач. RU: В статье проведена апробация методологии проверки на адекватность результатов математического моделирования функционирования специализированных ширококолейных агросредств мостового типа с использованием положений теории автоматического регулирования динамических систем. Проверку математических моделей горизонтальных и вертикальных колебаний специализированного ширококолейного агросредства на адекватность осуществлено путем сравнения теоретических и экспериментальных амплитудночастотных характеристик колебаний его курсового угла и поперечного смещения, а также теоретической и экспериментальной нормированных спектральных плотностей вертикальных колебаний его остова (как исходных величин) при отработке им входных возмущающих воздействий. Результатом количественной оценки исследуемых характеристик установлено, что согласно F-критерию Фишера ноль-гипотеза о равенстве сравниваемых дисперсий выходных величин не отклоняется. Удовлетворительное совпадение теоретических и экспериментальных результатов, а также положительный результат проверки математических моделей вертикальных и горизонтальных колебаний агросредства на адекватность указывает на возможность их дальнейшего использования для решения научных и практических задач. EN: The article methodology for checking adequacy of the results mathematical modeling functioning agricultural gantry systems for purposes using provisions of the theory automatic control dynamic systems are tested. For experimental registration of such parameters a agricultural gantry system, such as the characteristics of changes in its heading angle and vertical displacements and accelerations, an Android mobile communicator with built-in accelerometer sensors and Acceierometer Meter applications was used. The mathematical model of horizontal vibrations agricultural gantry system was checked for adequacy by comparing the theoretical and experimental amplitudefrequency characteristics of the oscillations its heading angle and lateral displacement (as initial values) when working out the input control action by it. The result of this check showed that in the operating frequency range (0...2) s-1, the difference between the oscillations of the input and output signals does not exceed 15%. A comparison of the theoretical and experimental normalized spectral densities of vertical vibrations of the skeleton agricultural gantry system use showed that both processes are characterized by approximately the same nature of the change in the frequency range. The difference in maximum theoretical and experimental dispersion is 1 s-1. As a result of a quantitative assessment of these studied characteristics, it was found that, according to the Fisher F-criterion, the zero hypothesis that the compared variances of the output variables are equal does not deviate both at the static significance level of 0.05 and 0.01. The satisfactory coincidence of the above theoretical and experimental results, as well as the positive result of checking the mathematical models vertical and horizontal vibrations of the agricultural gantry systems for purposes adequacy, indicates the possibility of their further use for solving scientific and practical problems.
Методология проверки математических моделей функционирования агромостовых систем на адекватность
Verification of mathematical models functioning of agricultural systems on adequacy
Keywords: ширококолійний агрозасіб; математичне моделювання; частотні характеристики; спектральна щільність; адекватність; мостовое агросредство; математическое моделирование; частотные характеристики; спектральная плотность; адекватность; agricultural gantry system; mathematical modeling; frequency characteristics; spectral density; adequacy